Optimization and enhancement of friction stir welding strength on high yield strength deformed steel. (2021) - Kumar, R.Senthil; Elango, V.; Giridharan, K.; Jothiprakash, V.M.; Stalin, B.
Abstract: In recent days, to increase the weld strength of the hard material was difficult. At the same time, more amounts of heats were generated and insufficient of welding joint was also occurred. The excess flow of heat may leads to damage the welded joints. Friction Stir Welding (FSW) with cooling arrangement was used to avoid the welding defects. The cooling system has been attached to the tool holder. It was used to manage or control the heat produced during welding process and its weld efficiency was also improved. Cubic Boron Nitride (CBN) tip was used to improve the welding strength and it was protects the tool life. The experimental investigation was conducted on High Yield Strength Deformed (HYSD) steel. FSW parametric effect and optimization was carried out by Taguchi method. The role of factors and their effects were studied through variance test and interaction plots. The comparison of weld strength was discussed with and without coating of CBN and cooling system.